Adult higher education : a case study on the workers' colleges in the People's Republic of China - Yü, Bo.; Xu, Hong Yan.; International Institute for Educational Planning (Paris : Unesco, International Institute for Educational Planning, 1988)
Conclusions (s. 99-105).
Part of the research on "The diversification of the educational field".
Keywords: aikuiskoulutus -- Kiina